2017
DOI: 10.1007/s12021-017-9343-z
|View full text |Cite
|
Sign up to set email alerts
|

SpiCoDyn: A Toolbox for the Analysis of Neuronal Network Dynamics and Connectivity from Multi-Site Spike Signal Recordings

Abstract: We implemented an automated and efficient open-source software for the analysis of multi-site neuronal spike signals. The software package, named SPICODYN, has been developed as a standalone windows GUI application, using C# programming language with Microsoft Visual Studio based on .NET framework 4.5 development environment. Accepted input data formats are HDF5, level 5 MAT and text files, containing recorded or generated time series spike signals data. SPICODYN processes such electrophysiological signals foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Functional connectivity and topological analysis . The FNCCH used to infer functional connectivity, as well as the metrics used to characterize the topological features of the cortical networks (Small-World Index, Clustering Coefficient, average shortest Path Length) were collected in an update version of the SpiCoDyn software [ 71 ].…”
Section: Methodsmentioning
confidence: 99%
“…Functional connectivity and topological analysis . The FNCCH used to infer functional connectivity, as well as the metrics used to characterize the topological features of the cortical networks (Small-World Index, Clustering Coefficient, average shortest Path Length) were collected in an update version of the SpiCoDyn software [ 71 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, the complexity and topology of commonly used in silico neural networks and thus the evaluation results can vary. For example, the accuracy of Transfer Entropy, a widely used algorithm for connectivity estimation, varies greatly depending on the model used for the evaluation [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas SII topologies are used in many evaluations, e.g. without delay times [15], with delay times, and with different use of STDP [16,17], more realistic scale-free topologies are rarely used for evaluations [3]. One can concluded that searching for the best algorithms can be confusing, since apparently better results are not synonymous with physiologic relevance for real biological neural networks.…”
Section: Discussionmentioning
confidence: 99%
“…We obtained connectivity matrix for each culture by applying the Filtered Cross-Correlation algorithm (Gorkin et al 2014, Pastore et al 2018) available in the free software SPICODYN (Pastore et al 2018, Bastle et al 2019). Cross correlograms were obtained using a bin size of 0.1 ms and a correlation window of 150 ms. Matrices were then analyzed using custom script in MATLAB.…”
Section: Methodsmentioning
confidence: 99%